2016
DOI: 10.1016/j.bpj.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Spanning Sequences in Endoplasmic Reticulum Proteins Promote Phospholipid Flip-Flop

Abstract: The mechanism whereby phospholipids rapidly flip-flop in the endoplasmic reticulum (ER) membrane remains unknown. We previously demonstrated that the presence of a hydrophilic residue in the center of the model transmembrane peptide sequence effectively promoted phospholipid flip-flop and that hydrophilic residues composed 4.5% of the central regions of the membrane-spanning sequences of human ER membrane proteins predicted by SOSUI software. We hypothesized that ER proteins with hydrophilic residues might pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…This led to the proposal that the interplay between transmembrane domains and non-bilayer favoring lipids might be sufficient to allow fast flip-flop in the ER [2123]. In line with these ideas, recent studies demonstrated that low-complexity synthetic transmembrane peptides are able to increase the rate of flipping of a variety of phospholipids in synthetic vesicles [24, 25]. However, a large number of peptide molecules were needed per vesicle to see this effect.…”
Section: Parameters Influencing Spontaneous Lipid Flip-flopmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the proposal that the interplay between transmembrane domains and non-bilayer favoring lipids might be sufficient to allow fast flip-flop in the ER [2123]. In line with these ideas, recent studies demonstrated that low-complexity synthetic transmembrane peptides are able to increase the rate of flipping of a variety of phospholipids in synthetic vesicles [24, 25]. However, a large number of peptide molecules were needed per vesicle to see this effect.…”
Section: Parameters Influencing Spontaneous Lipid Flip-flopmentioning
confidence: 99%
“…However, a large number of peptide molecules were needed per vesicle to see this effect. For example, reconstitution of 100 peptides/vesicle corresponding to the transmembrane protein EDEM1 could improve the rate of NBD-PC flipping to 20 lipids per second [25]. However, this contrasts with the rapid flipping seen when vesicles contain only one or a few copies of an authentic scramblase (see below).…”
Section: Parameters Influencing Spontaneous Lipid Flip-flopmentioning
confidence: 99%
“…In summary, we have shown that our synthetic DNA nanostructure can reproduce the biological function of a scramblase protein by inducing mixing of lipids that reside on opposite leaflets of a biological membrane in vitro and in human cells. Our synthetic DNA scramblase mixes lipids much more rapidly, outperforming both biological and reported artificial scramblases by at least three orders of magnitude 34,35 . Equipped with an activation mechanism and ability to target plasma membranes of specific cell types, our DNA scramblase can be made suitable for biomedical applications with the scrambling activity being controlled by the geometry of the toroidal lipid pore.…”
Section: Main Textmentioning
confidence: 83%
“…A direct role of spastin-M1 in limiting pre-LD formation is suggested by a study that tested the ability of a peptide comprising spastin-M1 membrane-spanning sequence to promote phospholipid transbilayer movement (flip-flop). Whereas the wild-type peptide increased the flip rate of lipids in artificial membranes, an R65A mutation abolished this ability (Nakao et al, 2016). It is conceivable that cells lacking spastin may have an excess of phospholipids at the cytoplasmic leaflet of the ER membrane, which could favor LD emergence (Chorlay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%